Incidence and risk of vaginal candidiasis associated with sodium–glucose cotransporter 2 inhibitors in real‐world practice for women with type 2 diabetes - Yokoyama, Hiroki (J Diabetes Investig, 2018)
AIMS/INTRODUCTION: The prevalence and risk of vaginal candidiasis before and after initiating sodium–glucose cotransporter 2 (SGLT2) inhibitors, although some clinical trials have been carried out, have not been adequately shown in real‐world practice. We investigated the incidence of vaginal Candida colonization and symptomatic vaginitis, and the clinical risk factors including diabetic microvascular complications. MATERIALS AND METHODS: The participants were 114 women with type 2 diabetes who were free of vaginitis symptoms and started SGLT2 inhibitors. Vaginal candidiasis tests through self‐administered swabs were carried out at baseline, 6 and 12 months. RESULTS: Before starting SGLT2 inhibitors, 17 participants (14.9%) had positive vaginal Candida colonization. Younger age and the presence of microangiopathy were significantly associated with the positive colonization in multivariate analysis. Among all participants, 23 (20.2%, 8 because of vaginitis and 15 for other reasons) discontinued SGLT2 inhibitors before reaching the 6‐month test. Of 65 participants who were negative for Candida at baseline and received the 6‐month test, 24 (36.9%) converted to a positive culture, and multivariate analysis showed older age as an independent risk for developing Candida colonization. There were 18 participants (15.8%) who developed symptomatic vaginitis, and they showed similar characteristics to the 24 participants. Most of those with negative cultures at 6 months showed negative results at 12 months and vice versa. CONCLUSIONS: The rates of developing positive colonization and symptomatic vaginitis after starting SGLT2 inhibitors appear to be higher in real‐world practice than the rates of 31% and 5–10% in clinical trials, respectively. Risk factors of vaginal Candida colonization might be different before and after taking SGLT2 inhibitors.